THE INFLUENCE OF COMPANY SIZE, MANAGERIAL SHARE OWNERSHIP,AND PROFITABILITY ON FIRM VALUE OF MANUFACTURING COMPANY LISTED ON BEI - ARDHA, ABINTA (Jurnal Ilmiah Mahasiswa FEB, 2018)
Â The primary goal of the company is to maximize firm value. Firm value is investor perception of the company's success rate, it is often associated with stock prices. This research aims to examine the effect of company Â size ,insider ownership, and profitability, towards the value of the company.This research uses secondary data, of the manufacturing companies which listed on BEI with periods 2014-2016. Research sample of 39 manufacturing companies, where the method used is purposive sampling is a sampling method that takes an object with the specified criteria. Analysis of the data used to analyze the factors that affect firm value is multiple regression analysis. The results of this research finds three independents variable have a significant effect on firm value . Three independents variable have significantly effect on firm value in this research: (i) company size is that of positive significant, (ii) managerial share ownership is that positive significant, (iii) profitability is that positive significant.Keywords : firm value, managerial share ownership, profitability, and company size